Myasthenia Gravis Related to Thymic Carcinoma: A Case Study - Lopes, Daniel Thomas Pereira; Gomes, Samila Marissa Pinheiro; Siqueira, Sheila Aparecida Coelho; Frassetto, Fernando Pereira; Sampaio, Pedro Henrique Martins Arruda; Moreno, Cristiane Araujo Martins; Rocha, Maria Sheila Guimarães; Estephan, Eduardo Paula (The Thoracic and Cardiovascular Surgeon Reports, 2020)
Myasthenia gravis and thymoma are often presented in association with ∼10% of myasthenic cases having concomitant thymoma. Thymic carcinoma is one of the rarest/aggressive human epithelial tumors and has no correlation with myasthenia gravis hitherto. Here is provided a clinical case and review of literature on a very rare association of thymic carcinoma (with no sign of thymoma) and myasthenia gravis (antiacetylcholine receptor antibody positive). Two years after thymectomy, clinical evolution was satisfactory. This clinical case elicits hypothesis that thymic carcinoma may be related with myasthenia gravis, what may have good prognostic from oncologic and neurologic perspectives.
Keywords: thymus; neurology/neurologic; thoracic surgery; pathology